SMART-C Intervention to Reduce Anxiety in Elementary School Students Experiencing Cyberbullying - Dian Veronika Sakti Kaloeti; Dinie Ratri Desiningrum (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2023)
This study was conducted to examine the effect of the SMART-C (Safe, Meeting, Accepting, Reliable, Tell-Children) intervention on reducing anxiety among elementary school students who had experienced cyberbullying. The research employed a quasi-experimental design with a one-group pretest-posttest approach, and the sample consisted of 20 participants who had been victims of cyberbullying. Parental consent was also obtained before allowing the participation of children in the intervention. The results showed that SMART-C training was effective in reducing anxiety (Z = -2.317, p < .03). The reduction was observed in overall (Z = -1.975, p < .04) and separation anxiety (Z = -2.420, p < .01). However, there was no significant change in the bullying condition before and after intervention. A significant difference also existed in anxiety scores between males and females after the treatment (t=.410; p<.05). Female children showed more significant decrease in anxiety (M = 18.57) compared to male (M = 17.15). Further studies on community intervention should be carried out to enhance digital literacy, involving children parents, teachers, and the community.